Mitigated viral myocarditis in A/J mice by the immunoproteasome inhibitor ONX 0914 depends on inhibition of systemic inflammatory responses in coxsackievirusB3 infection - Goetzke, Carl Christoph; Althof, Nadine; Neumaier, Hannah Louise; Heuser, Arndt; Kaya, Ziya; Kespohl, Meike; Klingel, Karin; Beling, Antje (Basic research in cardiology, 2021)
A preclinical model of troponin I-induced myocarditis (AM) revealed a prominent role of the immunoproteasome (ip), the main immune cell-resident proteasome isoform, in heart-directed autoimmunity. Viral infection of the heart is a known trigger of cardiac autoimmunity, with the ip enhancing systemic inflammatory responses after infection with a cardiotropic coxsackievirusB3 (CV). Here, we used ip-deficient A/J-LMP7−/− mice to investigate the role of ip-mediated effects on adaptive immunity in CV-triggered myocarditis and found no alteration of the inflammatory heart tissue damage or cardiac function in comparison to wild-type controls. Aiming to define the impact of the systemic inflammatory storm under the control of ip proteolysis during CV infection, we targeted the ip in A/J mice with the inhibitor ONX 0914 after the first cycle of infection, when systemic inflammation has set in, well before cardiac inflammation. During established acute myocarditis, the ONX 0914 treatment group had the same reduction in cardiac output as the controls, with inflammatory responses in heart tissue being unaffected by the compound. Based on these findings and with regard to the known anti-inflammatory role of ONX 0914 in CV infection, we conclude that the efficacy of ip inhibitors for CV-triggered myocarditis in A/J mice relies on their immunomodulatory effects on the systemic inflammatory reaction.